PROFIL TINGKAT KEBUGARAN JASMANI PADA ATLET JUNIOR PETANQUE KABUPATEN BATANGHARI - Putri Ihratun; Sukendro; Fitri Khairunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the physical fitness profiles of junior petanque athletes in Batanghari Regency. Physical fitness is a key factor that supports athletes’ physical ability to perform during training and competition. Good physical fitness can help athletes perform sports activities optimally and support the training process  by enhancing performance. Therefore, physical fitness measurements are necessary to objectively and measurably assess the physical condition of junior petanque athletes in Batanghari Regency. This study employed a quantitative descriptive method using a survey technique involving tests and measurements. The subjects of this study were junior petanque athletes in Batanghari Regency. The instrument used was the Nusantara Student Fitness Test (TKPN), which includes measurements of body composition (BMI), flexibility, muscle strength and endurance, as well as cardiorespiratory endurance. The research data was analyzed using descriptive statistics in the form of percentages to obtain an overview of the level of physical fitness of junior petanque athletes in Batanghari Regency based on the measurement results for each component of physical fitness. The results of the study indicate that the physical fitness levels of junior petanque athletes in Batanghari Regency vary and are not yet consistent across all components of physical fitness. Based on measurements using the Nusantara Student Fitness Test (TKPN), some athletes were still found to be in the moderate to poor categories for certain components, indicating that the athletes’ physical fitness is not yet fully optimal. This situation indicates the need for physical training and a more systematic, targeted, and sustainable exercise program to improve the physical fitness of junior petanque athletes in Batanghari Regency.